2014
DOI: 10.1016/j.celrep.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Tumoral Prolactin Receptor Promotes Autophagy-Related Cell Death

Abstract: Summary Therapeutic upregulation of macroautophagy in cancer cells provides an alternative mechanism for cell death. Prolactin (PRL) and its receptor (PRLR) are considered attractive therapeutic targets because of their roles as growth factors in tumor growth and progression. We utilized a novel antagonist peptide of PRL, G129R, to block activity of the tumoral PRL/PRLR axis, which resulted in inhibition of tumor growth in orthotopic models of human ovarian cancer. Prolonged treatment with G129R induced accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
1
33
1
2
Order By: Relevance
“…It interrupts the metabolic system in proliferative tumor cells, serving as an alternative or complementary mechanism to tumor suppression through induction of type II programmed cell death (43) (44). This cell growth inhibition via sustained autophagy mediated by FRα inhibition is a novel mechanism for cell death (21) and an important addition to the previous reports on cell cycle– and apoptosis-regulatory mechanisms, including inhibition of phosphatidylinositol-3 kinase and Akt during antibody-mediated tumor inhibition by transtuzumab (Herceptin) (45) and the immune effects of rituximab (46). Our studies also showed that MORAB-003 significantly augmented the antitumor effect of docetaxel through an autophagy-associated mechanism.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It interrupts the metabolic system in proliferative tumor cells, serving as an alternative or complementary mechanism to tumor suppression through induction of type II programmed cell death (43) (44). This cell growth inhibition via sustained autophagy mediated by FRα inhibition is a novel mechanism for cell death (21) and an important addition to the previous reports on cell cycle– and apoptosis-regulatory mechanisms, including inhibition of phosphatidylinositol-3 kinase and Akt during antibody-mediated tumor inhibition by transtuzumab (Herceptin) (45) and the immune effects of rituximab (46). Our studies also showed that MORAB-003 significantly augmented the antitumor effect of docetaxel through an autophagy-associated mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…Typically induced by prolonged stress, sustained autophagy eventually leads to cell death when protein and organelle turnover overwhelm the capacity of the cell (21). It interrupts the metabolic system in proliferative tumor cells, serving as an alternative or complementary mechanism to tumor suppression through induction of type II programmed cell death (43) (44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, by acquiring signals from 2 fluorescent constructs in real time, the rate of change in colocalization signal as a measure of the fusion rate and recycling rate between autophagosomes and lysosomes can be assessed. 354 Importantly, due to the integral dynamic relationship of autophagic flux with the onset of apoptosis and necrosis, it is advantageous to monitor cell death and autophagic flux parameters concomitantly over time, which FRET-based reporter constructs make possible. 355 In addition, as the metabolic control of autophagy is becoming increasingly clear, highlighting a tight network between the autophagy machinery, energy sensing pathways and the cell's metabolic circuits, 356,357 mitochondrial parameters such as fission and fusion rate as well as the cell's ATP demand should be monitored and correlated with autophagic flux data.…”
mentioning
confidence: 99%
“…Por isso, alguns investigadores acreditam que o PRLR pode ser possível alvo no desenvolvimento de novas terapias contra o câncer de mama (Wei et al, 2008;Fang et al, 2012;Wen et al, 2014).…”
unclassified
“…Outro problema é que essa terapia molecular aumente a autofagia e morte celular programada em tecido normal (Wen et al, 2014). Portanto, há necessidade do melhor entendimento do sinal celular da PRL e sua relação com modificações no citoesqueleto, bem como a proliferação e apoptose em cultura celular (Tallet et al, 2008).…”
unclassified